Composition for preparing perovskite as well as preparation method and application of composition

By introducing 2,2'-oxybis(ethylamine) additives into perovskite precursors and adjusting the molar ratios of lead iodide and cesium iodide, the problem of excessive width of the half-peak width of red PeLEDs is solved, achieving high Performance and spectral color-purity and stable deep red light PeLED improves the color purity and external quantum efficiency of the device.

CN119120008AInactive Publication Date: 2024-12-13WUYI UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411204024.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing red light metal halide perovskite light emitting diodes (PeLEDs) still have room for improvement in color purity and external quantum efficiency (EQE). The wider half-maximum width limits color gamut expansion, making it difficult to achieve high performance and spectrum A dark red light display device with pure and stable color.

Method used

By introducing low-cost 2,2'-oxybis(ethylamine) (OD) additives into perovskite precursors, adjusting the molar ratio of lead iodide and cesium iodide, and controlling the Pb2+ concentration in solution, prepare Deep red light PeLED with high performance and spectral chromatic stability.

Benefits of technology

The device's half-maximum width is ≤40nm and the external quantum efficiency reaches 10.0%, which significantly improves the color purity and stability of the device, and provides a simple and feasible method to achieve high-performance and spectral chromatic pure and stable deep red light PeLED. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005018516400000011
    Figure HDA0005018516400000011
  • Figure HDA0005018516400000012
    Figure HDA0005018516400000012
  • Figure HDA0005018516400000013
    Figure HDA0005018516400000013
Patent Text Reader

Abstract

The invention discloses a composition for preparing perovskite and a preparation method and application thereof.The preparation raw materials of a perovskite precursor solution comprise lead iodide, cesium iodide, 2-phenylethylamine hydriodate (PEAI) and 2, 2 '-oxybis (ethylamine). According to the invention, a low-cost 2, 2'-oxybis (ethylamine) (OD) additive is introduced into a perovskite precursor; and the deep red light perovskite light-emitting diode is successfully prepared. The half-peak width of a device prepared from the perovskite solution containing the 2, 2 '-oxybis (ethylamine) additive is smaller than or equal to 40 nm, the half-peak width of the device at the 685 nm position is specifically 38 nm, meanwhile, the EQE of the device can reach 10.0%, and a dark red light perovskite light emitting diode with high performance and pure and stable spectrum color is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of microelectronic devices, and in particular relates to a composition for preparing perovskite, a preparation method thereof and an application thereof. Background Art

[0002] As the demand for displays rises sharply, more stringent standards have been set for display technology, covering the pursuit of extreme color purity, improved energy efficiency, wider color gamut coverage, and ultra-high-definition resolution. In this context, metal halide perovskite materials have emerged in the field of light-emitting diodes (LEDs) with their excellent fluorescence quantum yield, excellent conductivity, narrow and tunable emission spectrum, flexible solution processing and low manufacturing cost, and are regarded as the direction of future display and lighting technology. In particular, red metal halide perovskite light-emitting diodes (PeLEDs), as the cornerstone optoelectronic devices for building full-color display systems, their performance is directly related to whether they can achieve high-standard color specifications such as Rec.2020. However, the current red PeLEDs still have significant room for improvement in color purity and external quantum efficiency (EQE), and their wide half-peak width (over 50nm) has become a key factor limiting the expansion of the color gamut. In order to break through this bottleneck and achieve wider color gamut coverage and excellent display quality, the scientific research community urgently needs to explore innovative strategies to reduce the half-width of red light PeLEDs, thereby pushing display technology to new heights. In order to meet the above challenges, a large number of scientific research teams have proposed many different innovative strategies. For example, a study fused phenylethylammonium and 1-naphthylmethylammonium cations in a molar ratio of 8:2 to successfully prepare a quasi-two-dimensional red light perovskite electroluminescent device, achieving an excellent red light emission with a wavelength of 661nm and a half-width of 52nm, demonstrating its progress in color regulation. Other studies have also achieved red light emission with a wavelength of 680nm and a half-width of only 39nm by finely controlling the molar ratio of organic salts to inorganic salts, especially the combination of benzylammonium iodide and cesium iodide and lead iodide, and achieved an external quantum efficiency of 6.23%, significantly improving device performance. Other studies have introduced potassium iodide to optimize the phase distribution of perovskite films, effectively reducing defects and weakening Cs + With [PbI6] 4- The interaction between the coordinated octahedra achieves red light emission with a wavelength of 679nm and a half-peak width of 56nm, and an external quantum efficiency of up to 8.61%. The above studies show that the half-peak width of red PeLEDs can be effectively reduced through component optimization engineering and additive engineering to achieve better color purity, but further exploration is still needed to achieve half-peak width (<50nm) and high-performance EQE display devices.

[0003] Therefore, there is an urgent need to provide a deep red perovskite light-emitting diode with pure and stable spectral color. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a composition for preparing perovskite, and the deep red light perovskite light-emitting diode prepared by the composition has the characteristics of high performance and spectral color purity and stability.

[0005] The invention also provides a method for preparing the calcium composition.

[0006] The present invention also provides a perovskite film, wherein the perovskite film is prepared from the composition.

[0007] The present invention also proposes a perovskite light-emitting diode, comprising a metal electrode layer, a hole injection layer, a hole transport layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a conductive glass layer stacked in sequence from top to bottom, wherein the perovskite light-emitting layer is the perovskite film.

[0008] According to a first aspect of the present invention, a composition for preparing perovskite is provided, wherein raw materials for preparing the composition include: lead iodide, cesium iodide, 2-phenylethylamine hydroiodide (PEAI) and 2,2'-oxybis(ethylamine).

[0009] The present invention introduces a low-cost 2,2'-oxybis(ethylamine) (OD) additive into a perovskite precursor, and successfully prepares a deep red light PeLED. The OD additive can effectively reduce the half-peak width of the electroluminescence (EL) of the display device, and achieve better color purity. The half-peak width of the device prepared by the perovskite solution containing the OD additive in the present invention is ≤40nm, and the half-peak width of the device at 685nm is specifically 38nm. At the same time, the EQE of the device can reach 10.0%. The present invention provides a simple and feasible new method for achieving high-performance and spectral color purity stable deep red light PeLED.

[0010] The 2,2'-oxybis(ethylamine) (OD) additive in the present invention directly plays an important role in the perovskite light-emitting layer. There are many defects such as halogen vacancy defects and dangling bonds in the shallow layer of the perovskite light-emitting layer. The 2,2'-oxybis(ethylamine) in the present invention has an inhibitory effect on these defects, thereby helping to achieve the preparation of a high-performance and spectrally pure and stable deep red light PeLED.

[0011] In some embodiments of the present invention, the lead iodide, the cesium iodide, the 2-phenylethylamine hydroiodide (PEAI) and the 2,2'-oxybis(ethylamine) are in a molar ratio of 1:1:0.7:0.064-0.106.

[0012] By precisely controlling the molar ratio of lead iodide and cesium iodide, the band gap energy and electronic structure of the perovskite can be adjusted, thereby optimizing the luminescence characteristics of the device; reducing defects and non-ideal structures in the material, and improving the stability and durability of the perovskite material; through appropriate PEAI doping, the energy level alignment of electrons and holes is adjusted, improving the effects of carrier injection and transport.

[0013] In some embodiments of the present invention, in the composition for preparing perovskite, in the solution state, Pb 2+ The concentration is 0.01-0.5mmol / ml.

[0014] Pb at the above concentration 2+ It helps to precisely control the crystal structure, composition uniformity and final physical and chemical properties of the material, improve the stability and durability of the material, optimize the energy band structure and electronic structure, and improve the efficiency and stability of the prepared perovskite light-emitting diode device.

[0015] According to a second aspect of the present invention, a method for preparing a composition is provided, comprising: mixing lead iodide, cesium iodide, 2-phenylethylamine hydroiodide and 2,2'-oxybis(ethylamine) in a solution state and heating.

[0016] In some embodiments of the present invention, the solvent in the cesium iodide solution is dimethyl sulfoxide.

[0017] In some embodiments of the present invention, in the solution of 2-phenylethylamine hydroiodide, the solvent is N,N-dimethylformamide.

[0018] In some embodiments of the present invention, in the solution of 2,2'-oxybis(ethylamine), the solvent is N,N-dimethylformamide.

[0019] In some embodiments of the present invention, the heating temperature is 30-80°C.

[0020] According to a third aspect of the present invention, a perovskite film is provided. The perovskite film is prepared from the composition for preparing perovskite.

[0021] In some embodiments of the present invention, the method for preparing the perovskite film comprises: spin coating and crystallizing a precursor solution of the perovskite composition and then annealing.

[0022] In some embodiments of the present invention, the rotation speed of the spin coating is 1000-5000 rpm, and the spin coating time is 30-100 s.

[0023] In some embodiments of the present invention, the spin coating step further comprises rapidly dropping a solution containing poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) during the 20-60 s of the spin coating to crystallize the film.

[0024] Adding poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) under the above conditions can form a more ordered and compact crystalline structure in the film, which helps to improve the carrier transport performance and photoelectric conversion efficiency of the film.

[0025] In some embodiments of the present invention, the concentration of the solution containing poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) is 0.1-20 mg / ml, and the solvent of the solution containing poly(9,9-dioctylfluorene-CO-N-(4-butylphenyl)diphenylamine) is 1,4-dioxane (DOA).

[0026] In some embodiments of the present invention, the annealing temperature is 50-150° C., and the annealing time is 0.1-10 min.

[0027] According to a fourth aspect of the present invention, a perovskite light-emitting diode is proposed, comprising a metal electrode layer, a hole injection layer, a hole transport layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a conductive glass layer stacked in sequence from top to bottom, wherein the perovskite light-emitting layer is the perovskite film.

[0028] In some embodiments of the present invention, the method for preparing the perovskite light-emitting diode comprises the following steps:

[0029] S1: After patterning the conductive glass using a laser etching process, ultrasonic cleaning of the conductive glass is performed using acetone, ethanol and deionized water in sequence;

[0030] S2: drying the cleaned conductive glass in an oven to obtain a conductive glass layer, and then immediately transferring the conductive glass to an environment filled with an inert atmosphere (which may be N2);

[0031] S3: depositing a solution of the electron injection layer on a conductive glass substrate by spin coating, and then performing an annealing treatment to obtain the electron injection layer;

[0032] S4: depositing a solution of the electron transport layer on the electron injection layer by spin coating, and then performing annealing to obtain the electron transport layer;

[0033] S5: depositing the prepared perovskite precursor solution on the electron transport layer by spin coating, and then performing annealing treatment to obtain a perovskite light-emitting layer;

[0034] S6: depositing a hole transport layer on the perovskite light-emitting layer by vacuum evaporation to obtain a hole transport layer;

[0035] S7: depositing a hole injection layer on the hole transport layer film by vacuum evaporation to obtain a hole injection layer film;

[0036] S8: depositing a metal electrode layer on the hole injection layer by vacuum evaporation to obtain a metal electrode layer.

[0037] In some embodiments of the present invention, the conductive glass substrate comprises a glass substrate with indium tin oxide (ITO) plated on its surface.

[0038] In some embodiments of the present invention, in step S1, the ultrasonic cleaning time is not less than 10 minutes.

[0039] In some embodiments of the present invention, in step S2, the drying time is 5-30 minutes, and the drying temperature is 100-150°C.

[0040] In some embodiments of the present invention, in step S3, the material of the electron injection layer includes lithium magnesium zinc oxide.

[0041] In some embodiments of the present invention, in step S3, the concentration of the solution of the electron injection layer is 10-20 mg / ml.

[0042] In some embodiments of the present invention, in step S3, the solvent of the solution of the electron injection layer includes anhydrous ethanol.

[0043] In some embodiments of the present invention, in step S3, the spin coating parameters include: a rotation speed of 3000-5000 rpm and a spin coating time of 30-120 s.

[0044] In some embodiments of the present invention, in step S3, the annealing temperature is 100-200° C., and the annealing time is 10-30 min.

[0045] In some embodiments of the present invention, in step S4, the material of the electron transport layer includes polyethyleneimine.

[0046] In some embodiments of the present invention, in step S4, the concentration of the solution of the electron transport layer is 0.1-10 mg / ml.

[0047] In some embodiments of the present invention, in step S4, the solvent of the solution of the electron transport layer includes anhydrous ethanol.

[0048] In some embodiments of the present invention, in step S4, the spin coating parameters include: a rotation speed of 3000-5000 rpm, a spin coating time of 30-120 s, and an annealing temperature of 50-150°C.

[0049] In some embodiments of the present invention, in step S6, the material of the hole transport layer includes 1,3,5-tri(4-[carbazol-9-yl]phenyl)amine.

[0050] In some embodiments of the present invention, in step S6, the pressure of the vacuum evaporation is: 5×10 -5 ~5×10 -4 The thickness of the vacuum-deposited film is 20-50 nm, and the rate of the vacuum-deposited film is

[0051] In some embodiments of the present invention, in step S6, the material of the hole transport layer includes 1,3,5-tri(4-[carbazol-9-yl]phenyl)amine.

[0052] In some embodiments of the present invention, in step S7, the material of the hole injection layer includes molybdenum trioxide.

[0053] In some embodiments of the present invention, in step S7, the pressure of the vacuum evaporation is 5×10 -5 ~5×10 - 4 Pa, the vacuum evaporation coating thickness is 1-20nm, the vacuum evaporation rate is

[0054] In some embodiments of the present invention, in step S8, the material of the metal electrode includes aluminum.

[0055] In some embodiments of the present invention, in step S8, the pressure of the vacuum evaporation is 5×10 -5 ~5×10 - 4 Pa, the vacuum evaporation coating thickness is 100-200nm, the vacuum evaporation rate is

[0056] In some embodiments of the present invention, the method for preparing the perovskite light-emitting diode further comprises packaging the prepared perovskite light-emitting diode.

[0057] In some embodiments of the present invention, the encapsulation step includes bonding the obtained device to a glass sheet using ultraviolet curing glue, and then irradiating it with a 365nm ultraviolet lamp for 20-60s for curing. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0059] Figure 1 The structure diagram of the perovskite light-emitting diode device prepared in Example 1;

[0060] Figure 2 The scanning electron microscope (SEM) results of the perovskite films of Example 1 and Comparative Example 1 are shown;

[0061] Figure 3 Graph showing experimental results of photoluminescence (PL) spectra of the perovskite films of Example 1 and Comparative Example 1;

[0062] Figure 4 The current density-voltage-brightness test result diagram of the perovskite light-emitting diodes of Example 1 and Comparative Example 1;

[0063] Figure 5 The external quantum efficiency and current efficiency test results of the perovskite light-emitting diodes of Example 1 and Comparative Example 1 are shown;

[0064] Figure 6 The electroluminescence spectra of the perovskite light-emitting diodes of Example 1 and Comparative Example 1 are shown;

[0065] Figure 7 The electroluminescence spectra of the perovskite light-emitting diodes of Example 1 and Comparative Example 1 at different operating voltages;

[0066] Figure 8 This is a graph showing the life test results of the perovskite light-emitting diodes of Example 1 and Comparative Example 1.

[0067] Fig. 9 The external quantum efficiency and current efficiency test results of the perovskite light-emitting diodes of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are shown; DETAILED DESCRIPTION

[0068] The words "preferably", "more preferably", etc. in the present invention refer to embodiments of the present invention that may provide certain beneficial effects in certain circumstances. However, other embodiments may also be preferred under the same circumstances or other circumstances. In addition, the description of one or more preferred embodiments does not imply that other embodiments are not applicable, nor is it intended to exclude other embodiments from the scope of the present invention.

[0069] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0070] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of the present invention.

[0071] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0072] Example 1

[0073] This embodiment provides a composition for preparing perovskite and a preparation method thereof and a perovskite light-emitting diode, specifically:

[0074] The preparation method of the perovskite composition is:

[0075] A1: Under nitrogen environment, first prepare 0.6mM / mL PbI2 (solvent DMF), 0.6mM / mL CsI (solvent DMSO), 0.15mM / mL OD (solvent DMF), 0.6mM / mL PEAI (solvent DMF) solution, and then mix them according to the molar ratio of PbI2: CsI: PEAI: OD = 1: 1: 0.7: 0.08. Finally, ensure that Pb 2+ The concentration of the prepared perovskite precursor solution is 0.12m mmol / mL. The prepared perovskite precursor solution is placed in a glove box filled with nitrogen and heated at 40°C for at least 10 hours in a dark environment to obtain a perovskite precursor solution after being fully stirred and dissolved.

[0076] The preparation method of perovskite light-emitting diode is as follows:

[0077] S1: Clean the transparent substrate by placing the ITO conductive glass in a beaker containing detergent, and ultrasonically clean it at 50°C for 1 hour, then clean it with deionized water for 3 times, each time for 10 minutes;

[0078] S2: The cleaned ITO conductive glass is then placed on a hot plate at 150°C for drying for 5 minutes, and finally subjected to plasma treatment for 15 minutes before being immediately placed in a glove box filled with nitrogen;

[0079] S3: The 14 mg / ml Li-MgZnO solution (solvent is anhydrous ethanol) prepared in advance is evenly added to the ITO surface using a pipette, and spin-coated at a speed of 3000 r / min for 30 seconds, and then placed on a hot stage and annealed at 140°C for 20 minutes to obtain an electron injection layer film;

[0080] S4: adding 0.5 mg / ml PEI solution to the cooled electron injection layer film, spin coating at a speed of 3000 r / min for 30 seconds, and then annealing at 80° C. on a hot plate for 5 minutes to obtain an electron transport layer film;

[0081] S5: The perovskite precursor solution was evenly dripped onto the surface of the electron transport layer on the cooled electron transport layer film, and the film was spin-coated at a speed of 3000 r / min for 76 seconds, and 0.5 mg / ml TFB solution was quickly dripped at 50 seconds, and then placed on a hot plate and annealed at 80°C for 3 minutes to obtain a perovskite light-emitting layer film;

[0082] S6: The hole transport layer TCTA is deposited on the light-emitting layer film by vacuum evaporation at a pressure of 5×10 -5 The deposition was carried out under the conditions of evaporation, the coating thickness was 30nm, and the rate was about A hole transport layer film is obtained;

[0083] S7: The hole injection layer MoO3 is deposited on the hole transport layer film by vacuum evaporation at a pressure of 5×10 -5 Pa conditions, the film thickness was 7nm, and the rate was about A hole injection layer thin film is obtained;

[0084] S8: The metal electrode Al layer is deposited on the electrode modification layer film by vacuum evaporation at a pressure of 5×10 -5 Pa conditions, the film thickness was 150nm, and the rate was about After obtaining the metal electrode Al, a perovskite light-emitting diode is obtained;

[0085] Finally, the perovskite light-emitting diode was packaged. After the glass sheet was bonded with UV-curing adhesive, it was irradiated with a 365nm ultraviolet lamp for about 30 seconds for curing. The packaging was completed to obtain the perovskite light-emitting diode device preparation.

[0086] Example 2

[0087] This embodiment provides a composition for preparing perovskite, a preparation method thereof, and a perovskite light-emitting diode. The difference between this embodiment and Example 1 is that the concentration of the OD additive mother solution in the perovskite precursor solution is 0.12mM / mL; the preparation scheme is mixed according to the molar ratio of PbI2:CsI:PEAI:OD=1:1:0.7:0.064, and the other conditions are the same.

[0088] Example 3

[0089] This embodiment provides a composition for preparing perovskite, a preparation method thereof, and a perovskite light-emitting diode. The difference between this embodiment and Example 1 is that the concentration of the OD additive mother solution in the perovskite precursor solution is 0.20mM / mL; the preparation scheme is mixed according to the molar ratio of PbI2:CsI:PEAI:OD=1:1:0.7:0.106, and the other conditions are the same.

[0090] Comparative Example 1

[0091] This comparative example provides a composition for preparing perovskite, a preparation method thereof, and a perovskite light-emitting diode. The difference between this comparative example and Example 1 is that no OD additive is introduced into the perovskite precursor solution, and other conditions are the same.

[0092] Comparative Example 2

[0093] This comparative example provides a composition for preparing perovskite, a preparation method thereof, and a perovskite light-emitting diode. The difference between this comparative example and Example 1 is that 2,2'-(ethylenedioxy)bis(ethylamine) (EDBE) is used in the perovskite precursor solution to replace the OD additive in Example 1, and the other conditions are the same, specifically:

[0094] A1: Under nitrogen environment, first prepare 0.6mM / mL PbI2 (solvent DMF), 0.6mM / mL CsI (solvent DMSO), 0.15mM / mL 2,2'-(ethylenedioxy)bis(ethylamine) (solvent DMF), 0.6mM / mL PEAI (solvent DMF) solution, and then mix them according to the molar ratio of PbI2: CsI: PEAI: EDBE = 1:1:0.7:0.08. Finally, ensure that Pb 2+ The concentration of the prepared perovskite precursor solution is 0.12mmol / mL, and the prepared perovskite precursor solution is placed in a glove box filled with nitrogen and heated at 40°C in a dark environment for at least 10 hours to fully stir and dissolve the solution to obtain the perovskite precursor solution;

[0095] The preparation method of perovskite light-emitting diode is as follows:

[0096] S1: Clean the transparent substrate by placing the ITO conductive glass in a beaker containing detergent, and ultrasonically clean it at 50°C for 1 hour, then clean it with deionized water for 3 times, each time for 10 minutes;

[0097] S2: The cleaned ITO conductive glass is then placed on a hot plate at 150°C for drying for 5 minutes, and finally subjected to plasma treatment for 15 minutes before being immediately placed in a glove box filled with nitrogen;

[0098] S3: The 14 mg / ml Li-MgZnO solution (solvent is anhydrous ethanol) prepared in advance is evenly added to the ITO surface using a pipette, and spin-coated at a speed of 3000 r / min for 30 seconds, and then placed on a hot stage and annealed at 140°C for 20 minutes to obtain an electron injection layer film;

[0099] S4: adding 0.5 mg / ml PEI solution to the cooled electron injection layer film, spin coating at a speed of 3000 r / min for 30 seconds, and then annealing at 80° C. on a hot plate for 5 minutes to obtain an electron transport layer film;

[0100] S5: The perovskite precursor solution was evenly dripped onto the surface of the electron transport layer on the cooled electron transport layer film, and the film was spin-coated at a speed of 3000 r / min for 76 seconds, and 0.5 mg / ml TFB solution was quickly dripped at 50 seconds, and then placed on a hot plate and annealed at 80°C for 3 minutes to obtain a perovskite light-emitting layer film;

[0101] S6: The hole transport layer TCTA is deposited on the light-emitting layer film by vacuum evaporation at a pressure of 5×10 -5 The deposition was carried out under the conditions of evaporation, the coating thickness was 30nm, and the rate was about A hole transport layer film is obtained;

[0102] S7: The hole injection layer MoO3 is deposited on the hole transport layer film by vacuum evaporation at a pressure of 5×10 -5 Pa conditions, the film thickness was 7nm, and the rate was about A hole injection layer thin film is obtained;

[0103] S8: The metal electrode Al layer is deposited on the electrode modification layer film by vacuum evaporation at a pressure of 5×10 -5 Pa conditions, the film thickness was 150nm, and the rate was about After obtaining the metal electrode Al, a perovskite light-emitting diode is obtained;

[0104] Finally, the perovskite light-emitting diode was packaged. After the glass sheet was bonded with UV-curing adhesive, it was irradiated with a 365nm ultraviolet lamp for about 30 seconds for curing. The packaging was completed to obtain the perovskite light-emitting diode device preparation.

[0105] Compared with Example 1, the perovskite light-emitting diode obtained in this comparative example changes the carrier transport characteristics of the perovskite material, such as the lifetime or mobility of electrons and holes, increases the recombination rate of charge carriers, and thus affects the energy spectrum purity and half-peak width during the light-emitting process.

[0106] Test Case

[0107] Figure 2 This is the result of a morphological analysis of the surface of the red light perovskite film using a scanning electron microscope (SEM). Figure 2 It can be found in (a) that the surface of the film without OD additive in Comparative Example 1 is uneven, and there are some irregular block areas, which will seriously affect the performance of the device. Figure 2 (b) is the film containing OD additive in Example 1, which is obviously smoother and more uniform, indicating that the addition of OD additive can improve the quality of perovskite film and promote the realization of high-performance devices.

[0108] Figure 3 The experimental results of the photoluminescence (PL) spectra of the perovskite films of Example 1 and Comparative Example 1 are shown. The perovskite films of Example 1 and Comparative Example 1 both show obvious PL emission peaks at 680 nm, and the half-peak width of the perovskite film P1 containing OD modification in Example 1 is 40 nm, which is 10 nm less than the half-peak width (50 nm) of the perovskite film without OD modification in Comparative Example 1, indicating that the addition of OD makes the film have a more concentrated light color and a higher color purity.

[0109] Figure 4 The current density-voltage-brightness test results of the perovskite device containing OD in Example 1 and without OD in Comparative Example 1 are shown. The current density of the perovskite device containing OD in Example 1 during device operation is significantly lower than that of the perovskite device without OD in Comparative Example 1, indicating that the electron injection process of the device modified by OD is smoother.

[0110] Figure 5 The results of external quantum efficiency and current efficiency of the devices containing OD in Example 1 and without OD in Comparative Example 1 are as follows. The maximum external quantum efficiency (EQE) of the perovskite device without OD in Comparative Example 1 is only 2.4%, while the maximum EQE of the perovskite device containing OD in Example 1 can reach 10.0%, indicating that the addition of OD significantly improves the performance of the device and reflects the effectiveness of the additive.

[0111] Figure 6The electroluminescence spectra of the device containing OD in Example 1 and the device without OD in Comparative Example 1 are as follows. The EL peak of the device containing OD additive is 685nm, and the EL peak of the device without OD additive is 682nm. By comparison, the EL half-width is obviously narrower after adding the OD additive, which is reduced from 43nm to 38nm after adding the OD additive, which fully demonstrates that the addition of OD additive can obtain a device with more concentrated light color.

[0112] Figure 7 The electroluminescence spectra of the device containing OD in Example 1 and the device without OD in Comparative Example 1 at different operating voltages are shown. When the operating voltage increases from 3.2V to 6V, the EL fronts of both devices are basically not shifted, which indicates that the addition of OD additives does not affect the shift of the device spectrum.

[0113] Figure 8 The device life test results of Example 1 with OD and Comparative Example 1 without OD. 2 Under the initial brightness condition, the time required for the brightness of the device to drop to 50% of the initial brightness value (T 50 ). The test found that the perovskite device T containing OD in Example 1 50 The half-life can reach 206.7min, while the perovskite device T without OD in comparative example 1 50 The half-life is only 33.2 min, which indicates that the introduction of OD additives can effectively improve the device operation time.

[0114] Fig. 9 The external quantum efficiency and current efficiency test results of the devices of Example 1, Example 2, Example 3, Comparative Example 1 without OD and Comparative Example 2 containing EDBE with different concentrations of OD are shown. The maximum EQE of Example 1 is 10.0%, the maximum EQE of Example 2 is 7.4%, the maximum EQE of Example 3 is 7.1%, the maximum EQE of Comparative Example 1 is 2.4%, and the maximum EQE of Comparative Example 2 is 6.4%. By comparison, it is shown that the OD concentration of Example 1 is the best and the best performance device can be obtained. At the same time, the EQE of the devices containing OD (Example 1, Example 2 and Example 3) are all greater than those without OD (Comparative Example 1) and those containing EDBE (Comparative Example 2), which further illustrates the effectiveness of OD additives and is superior to similar additives.

[0115] The above content describes the embodiments of the present invention in detail, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A composition for preparing perovskite, characterized in that: The raw materials for preparing the composition include: lead iodide, cesium iodide, 2-phenylethylamine hydroiodide and 2,2'-oxybis(ethylamine).

2. The composition according to claim 1, characterized in that In terms of molar ratio, the lead iodide, the cesium iodide, the 2-phenylethylamine hydroiodide and the 2,2'-oxybis(ethylamine) are 1:1:0.7:0.064-0.

106.

3. The composition according to claim 1, characterized in that In the solution state, in the composition, Pb 2+ The concentration is 0.01-0.5mmol / ml.

4. A method for preparing the composition according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: in a solution state, lead iodide, cesium iodide, 2-phenylethylamine hydroiodide and 2,2'-oxybis(ethylamine) are mixed and heated.

5. The method for preparing the composition according to claim 4, characterized in that: The heating temperature is 30-80°C.

6. A perovskite film, characterized in that: The perovskite film is prepared from the composition according to any one of claims 1 to 3.

7. The perovskite film according to claim 6, characterized in that: The method for preparing the perovskite film comprises: spin coating a precursor solution of the perovskite composition for crystallization and then annealing.

8. The perovskite film according to claim 7, characterized in that: The rotation speed of the spin coating is 1000-5000 rpm, and the time of the spin coating is 30-100 s.

9. A perovskite light-emitting diode, characterized in that: It comprises a metal electrode layer, a hole injection layer, a hole transport layer, a perovskite light-emitting layer, an electron transport layer, an electron injection layer and a conductive glass layer stacked in sequence from top to bottom, wherein the perovskite light-emitting layer is the perovskite film according to claim 7.

10. The perovskite light-emitting diode according to claim 9, characterized in that: The material of the hole transport layer includes 1,3,5-tri(4-[carbazol-9-yl]phenyl)amine.

Citation Information

Patent Citations

  • Organic-inorganic composite perovskite light-emitting diode device and fabrication method thereof

    CN109411614A

  • Laser multi-pulse generation method and application of metal halide perovskite multi-quantum well material in laser multi-pulse generation

    CN111769435A

  • Solvent atmosphere controlled perovskite in-situ film forming method, product thereof, and application of product

    CN113594396A